A VECX model of the Swiss economy - Katrin Assenmacher-Wesche; Mohammad Hashem Pesaran (Center for Economic Studies and ifo Institute (CESifo), 2008)
This paper applies the modelling strategy of Garratt, Lee, Pesaran and Shin (2003) to the estimation of a structural cointegrated VAR model that relates the core macroeconomic variables of the Swiss economy to current and lagged values of a number of key foreign variables. We identify and test a long-run structure between the variables. Moreover, we analyse the dynamic properties of the model using Generalised Impulse Response Functions. In its current form the model can be used to produce forecasts for the endogenous variables either under alternative specifications of the marginal model for the exogenous variables, or conditional on some pre-specified path of those variables (for scenario forecasting). In due course the Swiss VECX model can also be integrated within a Global VAR (GVAR) model where the foreign variables of the model are determined endogenously.
Keywords: C53; C32; 330; long-run structural vector autoregression; Prognoseverfahren; Zeitreihenanalyse; Makroökonomik; VAR-Modell; Schweiz